2017
DOI: 10.5812/ajcmi.41533
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Trichomoniasis in Pregnant Women Attending Hamadan City Health Centers in 2015

Abstract: Background: Trichomoniasis is one of the most non-viral sexually transmitted diseases worldwide that causes some complications such as adverse pregnancy outcomes. Objectives: The aim of this study was to determine the frequency of Trichomonas vaginalis infection among pregnant women in Hamadan, west of Iran. Methods: This study was conducted on 1200 pregnant women attending the Hamadan city health centers in 2015. After gathering socio-demographic characteristics and clinical signs and symptoms of the women, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Studies that have been conducted in pregnant women report prevalence rates ranging from 0% to approximately 20%. 2,6,7,1720 The prevalence of TV infection in this study was 12.9%. This result is similar to the prevalence found in a study that was conducted in Umlazi, South Africa, that showed a prevalence of 15.3% in pregnant women.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Studies that have been conducted in pregnant women report prevalence rates ranging from 0% to approximately 20%. 2,6,7,1720 The prevalence of TV infection in this study was 12.9%. This result is similar to the prevalence found in a study that was conducted in Umlazi, South Africa, that showed a prevalence of 15.3% in pregnant women.…”
Section: Discussionmentioning
confidence: 52%
“…Trichomoniasis is the most common curable STI, with a reported prevalence of 276.4 million infections annually worldwide. 13 In the African region, 42.8 million infections occur annually. 4 In South Africa, the estimated T. vaginalis (TV) infection prevalence ranges between 3.1% and 20.0%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichomoniasis is the most common STI with an estimated annual incidence of 276.4 million cases globally (Akbari and Matini 2017 ; Bouchemal et al 2017 ; Gatti et al 2017 ; Ramjee et al 2015 ). To the best of our knowledge, this study was the first to investigate the in vitro metronidazole resistance patterns in T. vaginalis isolates obtained from South African pregnant women and the correlation between the genotypes and drug susceptibility patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Trichomonas vaginalis is an anaerobic parasitic protozoan that causes the sexually transmitted infection (STI) trichomoniasis (Akbari and Matini 2017 ; Ramjee et al 2015 ). In sub-Saharan Africa, about 30 million infections occur annually (Naidoo and Wand 2013 ).…”
Section: Introductionmentioning
confidence: 99%